The Effect of CYP2D6 Drug–Drug Interactions on Hydrocodone Effectiveness. (24th August 2014) - Monte, Andrew A.; Heard, Kennon J.; Campbell, Jenny; Hamamura, D.; Weinshilboum, Richard M.; Vasiliou, Vasilis; Bird, Steven
Abstract Objectives The hepatic cytochrome 2D6 (CYP2D6) is a saturable enzyme responsible for metabolism of approximately 25% of known pharmaceuticals. CYP interactions can alter the efficacy of prescribed medications. Hydrocodone is largely dependent on CYP2D6 metabolism for analgesia, ondansetron is inactivated by CYP2D6, and oxycodone analgesia is largely independent of CYP2D6. The objective was to determine if CYP2D6 medication coingestion decreases the effectiveness of hydrocodone. Methods This was a prospective observational study conducted in an academic U.S. emergency department (ED). Subjects were included if they had self‐reported pain or nausea and were excluded if they were unable to speak English, were less than 18 years of age, had liver or renal failure, or carried diagnoses of chronic pain or cyclic vomiting. Detailed drug ingestion histories for the preceding 48 hours prior to the ED visit were obtained. The patient's pain and nausea were quantified using a 100‐mm visual analog scale (VAS) at baseline prior to drug administration and following doses of hydrocodone, oxycodone, or ondansetron. We used a mixed model with random subject effect to determine the interaction between CYP2D6 drug ingestion and study drug effectiveness. Odds ratios (ORs) were calculated to compare clinically significant VAS changes between CYP2D6 users and nonusers. Results A total of 250 (49.8%) of the 502 subjects enrolled had taken at least one CYP2D6 substrate, inhibitor, or inducing pharmaceutical, supplement, or illicit drug in the 48 hours prior to ED presentation. CYP2D6 drug users were one‐third as likely to respond to hydrocodone (OR = 0.33, 95% confidence interval [CI] = 0.1 to 0.8) and more than three times as likely as nonusers to respond to ondansetron (OR = 3.4, 95% CI = 1.3 to 9.1). There was no significant difference in oxycodone effectiveness between CYP2D6 users and nonusers (OR = 0.53, 95% CI = 0.3 to 1.1). Conclusions CYP2D6 drug–drug interactions appear to change effectiveness of commonly prescribed drugs in the ED. Drug–drug interaction should be considered prior to prescribing CYP2D6 drugs.